Modifications of grain-boundary structure by friction stir welding in the joint of nano-structured oxide dispersion strengthened ferritic steel and reduced activation martensitic steel. (August 2015) - Han, Wentuo; Chen, Dongsheng; Ha, Yoosung; Kimura, Akihiko; Serizawa, Hisashi; Fujii, Hidetoshi; Morisada, Yoshiaki
Abstract : The joint of oxide dispersion strengthened (ODS) ferritic steel and martensitic steel was produced by friction stir welding. The thermo-mechanical process during welding causes recrystallization in the ODS steel and phase transformation in the martensitic steel. In stir zones of both steels, low-angle boundaries significantly convert to high-angle boundaries. The recrystallization in ODS steel is characterized by the increase in the Σ3 twin boundary with an almost constant fraction of Σ5–Σ29 boundaries, while the martensitic steel shows an opposite trend.